The book of Jane - Habel, Jennifer (Iowa poetry prize., 2020)
"The Book of Jane is an investigation of gender, authority, and art. In spare and precise lines, and with a distinctively wry voice, Jennifer Habel draws a contrast between the archetype of the lone male genius and the circumscribed, relational lives of women. The collection revolves around the character Jane, whose actions and aspirations are inextricably tangled in the web of her responsibilities and relationships. Moments in Jane's ordinary life-in a kitchen, a passenger seat, a guest room-are rendered with wit, pathos, and charged ambivalence. Interwoven with depictions of Jane are poems in the voices of other women, both anonymous and well known. Throughout, Habel utilizes a remarkable array of forms and source materials"--